Cyclotraxin-B, a New Trkb Antagonist, and Glial Blockade by Propentofylline, Equally Prevent and Reverse Cold Allodynia Induced by Bdnf or Partial Infraorbital Nerve Constriction in Mice - Hernandez-Kunstmann, A; Constandil-Cordova, L (2012)
Several lines of evidence indicate that brain-derived neurotrophic factor (BDNF) plays a key role as a central pronociceptive modulator of pain, acting through postsynaptic TrkB receptors that trigger intracellular signaling cascades leading to central sensitization. The overall aim of this study was to investigate to what extent BDNF could participate in the generation and maintenance of trigeminal neuropathic pain. The results showed that acute intracisternal administration of nanogram doses of BDNF in naïve mice elicited long-lasting, dose-related, cold allodynic responses to topical application of acetone onto vibrissal pad skin. The systemic administration of cyclotraxin-B (CTX-B), a new TrkB receptor antagonist, or propentofylline, an inhibitor of glial activation, was able to either prevent or reverse the effects of intracisternal BDNF on cold nociception. In addition, the blockade of TrkB receptor by CTX-B inhibited the mechanisms that either initiate or maintain cold allodynia in the ipsilateral vibrissal pad skin after unilateral constriction of the infraorbital nerve. These observations raise the possibility that BDNF is capable on its own of conveying many features of the signaling mechanisms that underlie central sensitization caused by nerve constriction. Perspective: Although further studies are necessary to examine in detail the mechanisms underlying the strong anti-allodynic action of CTX-B, this compound may represent an interesting lead for the development of novel therapeutic strategies aimed at preventing and/or suppressing central sensitization associated with neuropathic pain. © 2012 by the American Pain Society.
Keywords: Trigeminal neuropathic pain; brain-derived neurotrophic factor; TrkB receptor antagonist; propentofylline; mice